PERLINDUNGAN HUKUM TERHADAP APOTEKER YANG MELAKUKAN HOME PHARMACY CARE DALAM HAL KEADAAN KEDARURATAN - Ardiyansyah Ardiyansyah (Faculty of Law, Universitas Lampung, 2020)
The legal protection of pharmacists is very important, because if there is no legal protection in carrying out pharmaceutical practices by a pharmacist it will become an obstacle in the running of pharmaceutical services to the public, especially with the new concept of pharmacy services at home (home pharmacy care). The instrument has not been regulated in the law so that the pharmacist profession is vulnerable to criminalization. The problem in this paper is (a) how is the legal protection of pharmacists in conducting home pharmacy care in the emergency services outside in their authority? How do you prevent the criminalization of pharmacists in conducting home pharmacy care? This study uses an empirical juridical and normative juridical approach. The results showed that the legal protection of pharmacists in carrying out home pharmacy care services in the emergency can carry out services outside their authority. The Indonesian Pharmacist Association (IAI) is obliged to provide protection to members as long as they carry out their duties in accordance with professional standards, professional service standards and operational procedure standards, and prevent the criminalization of pharmacists in practicing Home Pharmacy Care services. Suggestions by the authors in this study is expected the government to immediately issue a new law related to the validity of pharmacist activities in conducting home pharmacy care so that the existence of the law will guarantee legal certainty.